Potential of purple eggplant skin fraction (Solanum Melongena Var. Serpentinum L.) as an in vitro sunscreen - Sari, Salza Laila; Wulandari, Wulandari; Mutiara, Erlita Verdia (Journal of Health Management and Pharmacy Exploration, 2024)
Sunscreen is a product that is used as skin protection against sun exposure. The skin of purple eggplant is known to contain secondary metabolites which are used as sunscreens. This study aims to determine the activity of sunscreen fraction of the purple eggplant (Solanum melongena var. serpentinum L.) in vitro. Testing of sunscreen activity was carried out by calculating the value of SPF (Sun Protection Factor), %TE (Percent Transmission of Erythema) and %TP (Percent Transmission of Pigmentation) using the UV-Vis Spectrophotometry method. The purple eggplant skin fractionation method is by using LVC (Liquid Vacuum Chromatography). The results of the fractionation were identified using phytochemical screening and combined TLC. The fraction results were tested for SPF (Sun Protection Factor), %TE and %TP values. The results showed that the extract yield was 26.33%. The fractions used are fraction 9; 10; 11; and 12 which showed the same stain after being evaporated, which was a brownish yellow stain with a yield of 21,24%. The purple eggplant skin fraction (Solanum melongena var. serpentinum L.) has SPF, %TE and %TP values with optimal protection at a concentration of 400 ppm with each value obtained being 19; 1.35 and 9.79. The results of the statistical test of the purple eggplant skin fraction showed that the data were normally distributed but not homogeneous. The results of the homogeneity test for each concentration of results showed that the data were not significantly different.